A modified cuckoo search using different search strategies - HAKLI, HÃƒÂ¼seyin (Prof. Dr. Ismail SARITAS, 2016)
Cuckoo search (CS) is one of the recent population-based algorithms used for solving continuous optimization problems. The most known problem for optimization techniques is balancing between exploration and exploitation. CS uses two search strategies to updating the nest: local and global search.Ã‚Â Although cuckoo search are adequate for the exploration, it is not well enough the exploitation. Only one search equation is used for local search, this equation remains incapable and causes some deficiencies about the exploitation.Ã‚Â To enhance the ability of exploitation and to balance between global search and local search, different search strategies were implemented in CS algorithm. The proposed method was compared with basic CS on well-known unimodal and multimodal benchmark functions. Experimental results show that the proposed method is more successful than the basic CS in terms of solution quality.